«Ռոստամ Զալ» հայ-իրանական վեպի տարբերակներն ու ժանրային յուրահատկությունները - Համբարձումյան, Հայկ (ՀՀ ԳԱԱ Գրականության ինստիտուտ)
В статье представлена история записей, публикации и исследовании вариантов армяно-иранского эпоса «Ростам Зал». Также обозначены ареалы и пути распространения эпоса. Анализируются жанровые особенности эпоса «Ростaм Зал». Выделяются и обсуждаются жанровые признаки классического эпоса и их соотносимость к эпосу «Ростам Зал». В частности, национально- исторический фон, характер героизма, структурная целостность и идеологическое единство отдельных частей. The article presents the history of the recording, publication and research of variants of the Armenian- Iranian epic “Rostam Zal”. Also described arials and ways of spreading the epic.Analyzed the genre features of “Rostam Zal”. The genre features of the classic epic and their relevance to the “Rostam Zal” epic are highlighted and discussed. In particular, the national historical background, the nature of heroism, structural integrity and ideological unity of the separate parts. The main motifs of the epic “Rostam Zal” are compared with the similar motifs of the Armenian folk epic “Sasna Tsrer” and fairy tales. The nature of the commonalities and possible influences are also discussed. Mythological motives and the question of their links with Indo-European mythology are partially considered.
Keywords: Բանահյուսություն